2021
DOI: 10.1101/2021.01.21.427597
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NKCC1 modulates microglial phenotype, cerebral inflammatory responses and brain injury in a cell-autonomous manner

Abstract: The NKCC1 ion transporter contributes to the pathophysiology of common neurological disorders, but its function in microglia, the main inflammatory cells of the brain, has not been studied to date. Therefore, we generated a novel transgenic mouse line in which microglial NKCC1 was deleted. We show that microglial NKCC1 shapes both baseline and reactive microglia morphology and inflammatory responses. As opposed to systemic NKCC1 blockade, which decreased intracortical lipopolysaccharide (LPS)-induced cytokine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 118 publications
0
5
0
Order By: Relevance
“…However, such deletion only slightly affects the in vivo network dynamics or hippocampal-dependent behavioral tasks, suggesting that most of the effects observed in NKCC1 knock-out mice or after pharmacological blockade of the transporter, may be attributed to the loss of the protein from non-neuronal cells or from cells localized outside the brain (Graf et al, 2021 ). In the brain, NKCC1 has been found to be expressed in several non-neuronal cell types such as choroid plexus epithelial cells, astrocytes, oligodendrocytes and microglia (Tóth et al, 2021 ). In particular NKCC1 is highly expressed in microglia (DePaula-Silva et al, 2019 ) ( Figure 1 ) where it plays a fundamental role in neuro-inflammation.…”
Section: Distribution Of Nkcc1 and Kcc2mentioning
confidence: 99%
See 2 more Smart Citations
“…However, such deletion only slightly affects the in vivo network dynamics or hippocampal-dependent behavioral tasks, suggesting that most of the effects observed in NKCC1 knock-out mice or after pharmacological blockade of the transporter, may be attributed to the loss of the protein from non-neuronal cells or from cells localized outside the brain (Graf et al, 2021 ). In the brain, NKCC1 has been found to be expressed in several non-neuronal cell types such as choroid plexus epithelial cells, astrocytes, oligodendrocytes and microglia (Tóth et al, 2021 ). In particular NKCC1 is highly expressed in microglia (DePaula-Silva et al, 2019 ) ( Figure 1 ) where it plays a fundamental role in neuro-inflammation.…”
Section: Distribution Of Nkcc1 and Kcc2mentioning
confidence: 99%
“…In particular NKCC1 is highly expressed in microglia (DePaula-Silva et al, 2019 ) ( Figure 1 ) where it plays a fundamental role in neuro-inflammation. Thus, the selective deletion of NKCC1 on microglia affects their cell volume and baseline morphology and boosts cytokines production in response to inflammatory stimuli (Tóth et al, 2021 ). Interestingly, it has been recently reported that long-term potentiation triggers in potentiated synapses withdrawal of perisynaptic astrocytic processes, which involves the NKCC1 transporter and the actin-controlling protein cofilin.…”
Section: Distribution Of Nkcc1 and Kcc2mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, systemic administration of bumetanide has an anti‐inflammatory action outside the brain, whereas direct application into the brain in vivo has the opposite effect 44 . There are also intriguing findings obtained using low systemic doses of bumetanide and other diuretics in rodents (e.g., Krystal et al, 45 and Marguet et al 46 ) that point to beneficial actions, based on unidentified mechanisms outside the brain.…”
Section: Cellular Targets Of Bumetanide Outside the Brainmentioning
confidence: 99%
“…NKCC1 is also expressed in mature neurons, but the mRNA expression developmentally changes from a neuronal pattern at birth to a glial pattern (esp. oligodendrocytes and their precursors, endothelial cells, astrocytes and microglia) in adult mouse brain (Hübner et al, 2001a;Su et al, 2001;Wang et al, 2003;Zhang et al, 2014;Henneberger et al, 2020;Virtanen et al, 2020;Tóth et al, 2022). In glia cells, NKCC1 regulates for instance the proliferation and maturation of oligodendrocyte precursor cells in the adult mouse cerebellar white mater (Zonouzi et al, 2015) and modulates the microglial phenotype and inflammatory response (Tóth et al, 2022).…”
Section: Introductionmentioning
confidence: 99%